Comprehensive evaluation of endoscope performance involves balanced assessment, accurate feedback, and suggested improvements by endoscopists. Issue 5 (15th March 2021) - Katanuma, Akio; Kin, Toshifumi; Hayashi, Tsuyoshi
Abstract : This Editorial refers to the article by J.Y. Bang et al., p 822‐828 of this issue.